The effect of optimized reactive power dispatch and transformer tap setting condition in power system using evolutionary programming (EP) / Marlena Abu Samah - Abu Samah, Marlena (1997)
This report presents the effect of optimized reactive power dispatch and transformer tap setting condition in power system Evolutionary Programming (EP). The objective of this study is to determine the maximum amount of reactive power dispatch along with improving the tap setting transformer value in order to ensure the stability of power system by referring to the voltage stability index.